The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1809-29502012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Benefícios do decúbito ventral associado ao CPAP em recém-nascidos prematuros

Abstract: O objetivo deste estudo foi avaliar os benefícios nas variáveis clínicas do decúbito ventral (DV) associado a pressão positiva contínua nas vias aéreas (CPAP), em recém-nascido pré-termo (RNPT). Foi feito um estudo transversal em RNPT com utilização do CPAP internados na unidade de terapia intensiva (UTI). As frequências cardíaca (FC) e respiratória (FR), SpO2, quantificação do desconforto respiratório pelo boletim de Silverman e Andersen (BSA: quanto maior o valor, pior o desconforto respiratório) foram avali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
2
5
0
1
Order By: Relevance
“…However, this finding was present in less than half (25.8%) of our sample, and it was the presence of respiratory distress the main indication for the babies' hospitalization. The pulmonary immaturity of this population hinders the gas exchange and makes the dyspnea the main sign in newborn infants after birth, which may justify our results 20 . Almost half of our sample needed the use of vasoactive drugs and the vast majority required the use of a ventilatory support, moreover, they had a prolonged hospitalization with excessive time in therapy.…”
Section: Referencessupporting
confidence: 64%
See 2 more Smart Citations
“…However, this finding was present in less than half (25.8%) of our sample, and it was the presence of respiratory distress the main indication for the babies' hospitalization. The pulmonary immaturity of this population hinders the gas exchange and makes the dyspnea the main sign in newborn infants after birth, which may justify our results 20 . Almost half of our sample needed the use of vasoactive drugs and the vast majority required the use of a ventilatory support, moreover, they had a prolonged hospitalization with excessive time in therapy.…”
Section: Referencessupporting
confidence: 64%
“…Ibuprofen is a therapeutic alternative for the closure of PDA 18.19 . In several controlled and randomized clinical trials, ibuprofen was as effective as indomethacin in the promotion of the closing of the canal, and had less effect on mesenteric, renal and cerebral perfusions 18,20 .…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The premature neonates has characteristics that can compromise the realization of the gas exchanges, and as characteristics of this group the disadvantages resulting from the immaturity of the respiratory system and the disadvantages in the respiratory mechanics. 17,18 A study conducted in the State of Piauí, which had as objective to determine the association between the predisposing factors of the admission of the newborn in the NITU and the maternal characteristics, demonstrated that 57.2% (n=215) of the neonates presented some respiratory problem as a diagnosis to its admission. 19 This relationship between the prematurity and the respiratory disturbances was emphasized in the statements of the interviewees, when these report that as soon as the neonates are admitted, at the time of the data collection they seek initially information that allow reference to some of these two characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…12 Os RN apresentam características anatômicas e fisiológicas (como retificação do músculo diafragma e das costelas, a instabilidade nas vias aéreas, da caixa torácica, e do abdômen, etc.) 13 que predispõem o desenvolvimento de distúrbios do sistema respiratório (alguns dos quais associados a quadros álgicos, como as pneumonias, derrames pleurais), os quais podem requerer a necessidade de intubação endotraqueal, e complicações, como lesões traqueais e quadros inflamatórios em vias aéreas superiores. 14 Rev.…”
Section: Introductionunclassified